Women's Rights in Islamic Jurisprudence - Saulia Rohimah Kumullah; Deddy Ramdhani (Penelitian dan Pengembangan Ilmu, 2024)
In the context of this research, researchers explore the concept of gender equality in Islam through a systematic literature review. This research aims to provide a better understanding of the evolution of views on women's rights in Islamic jurisprudence, with a focus on contemporary fatwas issued by major religious authorities in various Muslim-majority countries. Researchers conducted an analysis of relevant literature from reputable international databases, using established inclusion and exclusion methods, and following the PRISMA framework. The results of the discussion show that the concept of gender equality in Islam is a complex and continuously developing topic, influenced by various social, cultural and religious factors in Muslim society. Traditional interpretations often limit the role and position of women, but there is an evolution of views that emphasize the principles of equality, justice and the same human dignity between men and women. The implication of this research is the importance of supporting a more inclusive interpretation of Islam towards women's rights, as well as strengthening progressive social change in Muslim societies.